A Quantitative Study on User Experience Dimensions and Their Impact on User Satisfaction in Indonesian Mobile E-Commerce - Saputra, Afif Dwi; Tarigan, Riswan E.; Wijaya, Yoana Sonia (International Journal of Informatics and Information Systems, 2024)
This research examines how user experience (UX) dimensions influence user satisfaction in Indonesia’s mobile e-commerce ecosystem. As mobile shopping continues to dominate digital transactions, understanding the relationship between UX and user satisfaction becomes crucial for maintaining platform competitiveness. Adopting a quantitative explanatory approach, the study gathered data from 100 active users of leading e-commerce platforms such as Shopee, Tokopedia, and Lazada through an online questionnaire. The instrument was based on the User Experience Questionnaire (UEQ) framework, encompassing six dimensions—Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, and Novelty—with user satisfaction serving as the dependent variable measured via validated Likert-scale indicators. Analytical procedures included descriptive analysis, reliability and validity tests, and multiple linear regression using SPSS version 26. The findings reveal that five out of six UX dimensions significantly and positively affect user satisfaction (p 0.05). Among them, Perspicuity and Efficiency exert the strongest influence, underscoring the importance of intuitive interface design and smooth, error-free transaction processes. Dependability, Attractiveness, and Stimulation also play notable roles, indicating that both functional performance and emotional engagement contribute to favorable user experiences. Conversely, Novelty—though positively associated—does not reach statistical significance, implying that while users appreciate innovation, they prioritize clarity and reliability. The regression model yields an R² value of 0.742, suggesting that UX dimensions collectively account for 74.2% of the variance in user satisfaction. Overall, the study affirms that UX is a decisive factor in shaping user satisfaction and loyalty in mobile e-commerce environments. It enriches existing UX scholarship by providing empirical evidence from Indonesia’s fast-growing digital market. Practically, the results encourage developers to emphasize usability, dependability, and aesthetic design to maintain user engagement. Future studies are recommended to integrate trust, emotional attachment, and emerging technologies such as artificial intelligence and augmented reality to obtain a more comprehensive understanding of user satisfaction in digital commerce.